The pro-inflammatory signalling regulator Stat4 promotes vasculogenesis of great vessels derived from endothelial precursors - Zhao-Zheng Meng (Nature Portfolio, 2017)
Stat4 is a transcription factor known to regulate pro-inflammatory signalling. Here, Menget al. show that Stat4 is not only regulating inflammation but it is also crucial for great vessels development and endothelial precursor proliferation in zebrafish, by inhibiting the expression of hdac3and counteracting the effect of Stat1a.